Web page design - Stubbs, S. Todd (South-Western Pub., 2000)
Offering essential preparation for using any Web page design software, this text provides a common-sense approach to design fundamentals and emphasizes using a Web home page to capture a particular audience. Each project gives students an opportunity to enhance their personal Web portfolio. This text includes critical analysis of Web page organization, design, and functionality. 15+ hours of instruction